The Effect of Electronic Tax Invoice Implementation, Tax Return Submission in the Coretax System, and Tax Penalties on VAT Compliance with Taxpayer Awareness as a Mediating Variable - Cahyani, Tirta Nirmala; Triwarti, Hairul (Amkop Management Accounting Review (AMAR), 2025)
This study investigates the influence of Electronic Tax Invoice Implementation, SPT Submission in the Coretax System, and Tax Sanctions on VAT Compliance, with Taxpayer Awareness as a mediating variable. Utilizing a quantitative approach through an explanatory survey, the research focuses on VAT revenue at KPP Pratama Jakarta Pancoran, using primary data collected from questionnaires distributed to 100 Corporate Taxpayers (PKP) registered at the office, covering the period from 2020 to 2025. The sample was determined using the Lemeshow (1997) formula and purposive sampling technique. Data analysis was conducted using SmartPLS version 4.0 with the Partial Least Square (PLS-SEM) method. Results indicate that Electronic Tax Invoice Implementation significantly positively affects VAT compliance, as does SPT Submission in the Coretax System. Tax Sanctions also show a significant positive effect on VAT compliance. Additionally, Electronic Tax Invoice Implementation, SPT Submission, and Tax Sanctions can mediate Taxpayer Awareness, each having a significant positive impact on VAT compliance. These findings highlight the importance of these factors in enhancing taxpayer compliance in Indonesia.